Chemosensitivity of BRCA1-Mutated Ovarian Cancer Cells and Established Cytotoxic Agents. Issue 8 (1st October 2017) - van Haaften, Caroline; van Eendenburg, Jaap; Boot, Arnoud; Corver, Willem E.; Haans, Lucien; van Wezel, Tom; Trimbos, J. Baptist
Abstract : Objective: Serous adenocarcinomas that arise in patients with inherited mutations in the tumor suppressor genes BRCA1 and BRCA2 are initially well treatable with platinum/paclitaxel. For recurrent disease in patients with BRCA1 or BRCA2 mutations, olaparib treatment is available. To study additional therapeutic regimens, a better understanding of the cellular and molecular mechanisms of the tumors in in vitro models is important. Methods/Materials: From a high-grade serous ovarian tumor of a BRCA1 mutation carrier, we established 3 distinct cell line subclones, OVCA-TR3.1, -2, and -3. Immunohistochemical characterization, flow cytometric analyses, chemosensitivity, and somatic mutation profiling were performed. Results: The cell lines expressed AE1/AE3, Pax8, WT-1, OC125, estrogen receptor (ER), and p53, comparable to the primary tumor. Synergism could be shown in the combination treatment eremophila-1-(10)-11(13)-dien-12, 8β-olide (EPD), with cisplatin, whereas combination with olaparib did not show synergism. Eremophila-1-(10)-11(13)-dien-12, 8β-olide, a sesquiterpene lactone, is a novel chemotherapeutic agent. The inherited BRCA1 c.2989_2990dupAA mutation was confirmed in the cell lines. Loss of heterozygosity of BRCA1 was detected in each cell line, as well as a homozygous TP53 c.722C>A mutation. Flow cytometry showed that all cell lines had a distinct DNA index. Conclusions: Three new isogenic ovarian cancer cell lines were developed from a patient with a germ line BRCA1 mutation. Chemosensitivity profiling of the cell lines showed high tolerance for olaparib. Treatment with EPD proved synergistic with cisplatin. The effects of EPD will be further investigated for future clinical efficacy.